Investigation of UV Dye-Sensitized Solar Cells Based on Water Electrolyte: A New Insight for Wavelength-Selective Greenhouse - Daiana Albulescu; Daniel Ursu; Lucian-Mircea Rusnac; Sabina Nitu; Marinela Miclau; Melinda Vajda (Crystals, 2022)
The optimization of the photoactive electrode based on TiO2 with a complex architecture for UV dyes along with water-based electrolyte has successfully allowed us (i) to obtain a photovoltaic efficiency of the dye-sensitized solar cell with 1.45 times higher than the best efficiency reported for synthetic dye and 3 times for curcumin dye so far; (ii) transparency on the entire Photosynthetic Active Radiation domain; (iii) preserving high efficiency for lighting 1 sun (summer) and shading, especially for 60 mW/cm2, which represents the maximum illumination in the rest of the seasons. Our water-based dye-sensitized solar cells loaded with synthetic and natural UV dyes have revealed that the implementation of a dye-sensitized solar cell in autonomous greenhouses is a viable and inexpensive concept.